Case Study of the Response of N(6)-Methyladenine DNA Modification to Environmental Stressors in the Unicellular Eukaryote Tetrahymena thermophila - Sheng, Yalan (mSphere, 2021)
Rediscovered as a potential epigenetic mark, N(6)-methyladenine DNA modification (6mA) was recently reported to be sensitive to environmental stressors in several multicellular eukaryotes. As 6mA distribution and function differ significantly in multicellular and unicellular organisms, whether and how 6mA in unicellular eukaryotes responds to environmental stress remains elusive. Here, we characterized the dynamic changes of 6mA under starvation in the unicellular model organism Tetrahymena thermophila. Single-molecule, real-time (SMRT) sequencing reveals that DNA 6mA levels in starved cells are significantly reduced, especially symmetric 6mA, compared to those in vegetatively growing cells. Despite a global 6mA reduction, the fraction of asymmetric 6mA with a high methylation level was increased, which might be the driving force for stronger nucleosome positioning in starved cells. Starvation affects expression of many metabolism-related genes, the expression level change of which is associated with the amount of 6mA change, thereby linking 6mA with global transcription and starvation adaptation. The reduction of symmetric 6mA and the increase of asymmetric 6mA coincide with the downregulation of AMT1 and upregulation of AMT2 and AMT5, which are supposedly the MT-A70 methyltransferases required for symmetric and asymmetric 6mA, respectively. These results demonstrated that a regulated 6mA response to environmental cues is evolutionarily conserved in eukaryotes. IMPORTANCE Increasing evidence indicated that 6mA could respond to environmental stressors in multicellular eukaryotes. As 6mA distribution and function differ significantly in multicellular and unicellular organisms, whether and how 6mA in unicellular eukaryotes responds to environmental stress remains elusive. In the present work, we characterized the dynamic changes of 6mA under starvation in the unicellular model organism Tetrahymena thermophila. Our results provide insights into how Tetrahymena fine-tunes its 6mA level and composition upon starvation, suggesting that a regulated 6mA response to environmental cues is evolutionarily conserved in eukaryotes.